Impacts of reproductive systems on grapevine genome and breeding - Hua Xiao; Yue Wang; Wenwen Liu; Xiaoya Shi; Siyang Huang; Shuo Cao; Qiming Long; Xu Wang; Zhongjie Liu; Xiaodong Xu; Yanling Peng; Pengfei Wang; et al. (Nature Communications)
Abstract Diversified reproductive systems can be observed in the plant kingdom and applied in crop breeding; however, their impacts on crop genomic variation and breeding remain unclear. Grapevine (Vitis vinifera L.), a widely planted fruit tree, underwent a shift from dioecism to monoecism during domestication and involves crossing, self-pollination, and clonal propagation for its cultivation. In this study, we discover that the reproductive types, namely, crossing, selfing, and cloning, dramatically impact genomic landscapes and grapevine breeding based on comparative genomic and population genetics of wild grapevine and a complex pedigree of Pinot Noir. The impacts are widely divergent, which show interesting patterns of genomic purging and the Hill-Robertson interference. Selfing reduces genomic heterozygosity, while cloning increases it, resulting in a “double U-shaped” site frequency spectrum (SFS). Crossing and cloning conceal while selfing purges most deleterious and structural burdens. Moreover, the close leakage of large-effect deleterious and structural variations in repulsion phases maintains heterozygous genomic regions in 4.3% of the grapevine genome after successive selfing for nine generations. Our study provides new insights into the genetic basis of clonal propagation and genomic breeding of clonal crops by purging deleterious variants while integrating beneficial variants through various reproductive systems.